Mitochondrial DNA copy number variation and pancreatic cancer risk in the prospective EPIC cohort - Gentiluomo, M; Katzke, V; Kaaks, R; Schmidt, J; Et al. (American Association for Cancer Research, 2020)
Background: Mitochondrial DNA (mtDNA) copy number in peripheral blood has been found to be associated with risk of developing several cancers. However, data on pancreatic ductal adenocarcinoma (PDAC) are very limited.